Anti-inflammatory and analgesic activities of acetophenone semicarbazone and benzophenone semicarbazone - Zahan, Ronok; Ali, Shaikh M Mohsin; Jesmin, Mele; Azad, M Abul Kalam; Islam, M Khairul (© 2012 Asian Pacific Tropical Biomedical Magazine., 2016)
This article was published in Asian Pacific Journal of Tropical Biomedicine [© 2012 Asian Pacific Tropical Biomedical Magazine] and the definite version is available at : http://www.apjtb.com/zz/2012s2/103.pdf The article website is at: http://www.journals.elsevier.com/asian-pacific-journal-of-tropical-biomedicine/